2019
DOI: 10.1097/sla.0000000000003731
|View full text |Cite
|
Sign up to set email alerts
|

Tradition Versus Value: Is There Utility in Protocolized Postoperative Laboratory Testing After Elective Colorectal Surgery?

Abstract: Objective:Determine if routine ordering of postoperative day 1 (POD 1) serum laboratory tests after elective colorectal surgery are clinically warranted and valuable given the associated costs of these lab tests.Summary of Background Data:Routine postoperative serum laboratory tests are a part of many colorectal surgery order sets. Whether these protocolized lab tests represent cost-effective care is unknown.Methods:Patients undergoing elective colorectal surgery between January 1, 2015 and December 31, 2017 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In 2008, Stuebing et al 37 performed a study in which they raised awareness of phlebotomy costs to surgeons and surgical house staff via weekly announcements and observed a savings of $54,967 inpatient charges over 11 weeks. In their study, McKenna et al 19 used the Centers for Medicare and Medicaid Services outpatient laboratory fee schedule to estimate a total cost excess of $64,000 for POD1 laboratory tests of approximately 2300 patients. To establish a realistic cost savings estimate, we elected to use inpatient costs to the hospital, which can vastly differ from the generally higher charges to patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, Stuebing et al 37 performed a study in which they raised awareness of phlebotomy costs to surgeons and surgical house staff via weekly announcements and observed a savings of $54,967 inpatient charges over 11 weeks. In their study, McKenna et al 19 used the Centers for Medicare and Medicaid Services outpatient laboratory fee schedule to estimate a total cost excess of $64,000 for POD1 laboratory tests of approximately 2300 patients. To establish a realistic cost savings estimate, we elected to use inpatient costs to the hospital, which can vastly differ from the generally higher charges to patients.…”
Section: Discussionmentioning
confidence: 99%
“…34 In 1999, Skenderis et al 35 examined postoperative testing in a cohort of 105 patients with colorectal cancer and found that only 1.4% of laboratory tests required intervention. More than 2 decades later, McKenna et al 19 published their outcomes from investigating specifically POD1 laboratory tests of 2252 patients undergoing elective colorectal surgery. They found that 96% of POD1 laboratory test results were normal, and only 1% of abnormal results required intervention, which led to a practice shift at their institution toward the elimination of routine POD1 laboratory test, except in select patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKI within 24 hours after the operation was reported as it is standard practice in our institution to check postoperative creatinine at this time and rarely required rechecking. 15,16 Of note, patients with lacking preor postoperative creatinine were excluded. Prolonged LOS was defined as LOS !7 days.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of AKI was based on the Kidney Disease Improving Global Outcomes criteria 14 : increase of postoperative serum creatinine ≥0.3 mg/dL compared to preoperative creatinine within 48 hours or ≥1.5 increase from the baseline which is known or presumed to have occurred within the previous 7 days. AKI within 24 hours after the operation was reported as it is standard practice in our institution to check postoperative creatinine at this time and rarely required rechecking 15,16 . Of note, patients with lacking pre- or postoperative creatinine were excluded.…”
Section: Methodsmentioning
confidence: 99%